An insulating polyimide-glass blended woven tape and its preparation method and application
Patent Information
- Application Number
- CN202611221375.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-13
AI Technical Summary
[0008]本发明的目的在于提供一种绝缘的聚酰亚胺-玻纤混纺编织带,以解决现有技术中聚酰亚胺薄膜与玻璃纤维编织带物理层合所导致的界面热阻大、浸渍不均匀、工艺复杂及力学协同性差等问题
1.热管理性能提升:聚酰亚胺长丝与玻纤在纱线内部微观交织,形成了连续、无显著界面的三维热传导网络,有效降低了传统层合结构中的界面热阻,有利于超导线圈运行中热量的快速耗散,提升了磁体稳定性。
Smart Images

Figure CN122907452A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-field superconducting magnet insulation technology, and particularly to an insulating polyimide-glass fiber blended braided tape, its preparation method, and its application. Background Technology
[0002] Superconducting coils are core components of high-field magnet devices (such as nuclear magnetic resonance imaging (NMR) machines, particle accelerators, and nuclear fusion experimental devices). Their insulation systems must maintain reliable electrical insulation, excellent mechanical support, and efficient thermal conductivity over long periods of time in harsh environments including extreme low temperatures of 4.2K liquid helium, strong magnetic fields, high mechanical stress, and complex electromagnetic cycles.
[0003] Currently, most mainstream superconducting coil insulation employs a composite structure of polyimide film and glass fiber braided tape. This structure is typically achieved by alternating or parallel winding of polyimide film tape and glass fiber braided tape. While this approach combines the high insulation properties of polyimide with the high strength of glass fiber, the following problems still exist in long-term practical application: 1. Interface thermal resistance problem: There is a physical interface between the thin film and the braided tape, which hinders the conduction of heat along the cross-sectional direction of the coil and affects the thermal stability of the magnet under conditions such as loss of quench.
[0004] 2. Risk of uneven impregnation: The stacking of multiple heterogeneous materials may create microscopic obstacles to the flow and capillary penetration of the low-temperature impregnation resin, which can easily lead to poor local impregnation and the formation of air gaps or weak points.
[0005] 3. High process complexity: The film and fiberglass tape need to be processed separately and precisely stacked, which is complicated and limits production efficiency. Furthermore, misalignment between layers may affect the uniformity of insulation.
[0006] 4. Insufficient mechanical synergy: The mechanical properties (such as modulus and elongation at break) of the film and glass fiber differ significantly. Under the repeated action of low-temperature thermal shrinkage and electromagnetic force, stress concentration is easily generated at the interface, which may lead to the initiation of microcracks.
[0007] Therefore, there is an urgent need to develop a new type of insulating material that is integrated, more isotropic, and has enhanced interface properties to improve the overall reliability of superconducting coils. Summary of the Invention
[0008] The purpose of this invention is to provide an insulating polyimide-glass fiber blended woven tape to solve the problems of high interfacial thermal resistance, uneven impregnation, complex process and poor mechanical synergy caused by the physical lamination of polyimide film and glass fiber woven tape in the prior art.
[0009] The present invention also aims to provide a preparation method for preparing an integrated, more isotropic, and interfacially enhanced insulating polyimide-glass fiber blended woven tape.
[0010] Another objective of this invention is to provide the application of polyimide-glass fiber blended braided tape in the inter-turn insulation, interlayer insulation, or ground insulation of superconducting coils.
[0011] In a first aspect, the present invention discloses an insulating polyimide-glass fiber blended braided tape, the braided tape being woven from yarns made by blending polyimide filaments and glass fiber filaments; The mass ratio of polyimide filament to glass fiber filament is (30-50):(70-50).
[0012] Preferably, the polyimide filament is a thermoplastic polyimide filament with a glass transition temperature of not less than 250°C.
[0013] Preferably, the glass fiber filaments are alkali-free glass fiber (E-glass) or high-strength glass fiber (S-glass), with a single filament diameter of 5 to 13 μm.
[0014] Preferably, the blended yarn includes one of ring spinning, Siro spinning and wrapping spinning; when the wrapping spinning process is used, the polyimide filament is the core yarn and the glass fiber filament is the covering yarn.
[0015] Preferably, the woven tape has a plain weave, twill weave, or satin weave structure, with a thickness of 0.05–0.20 mm and a width of 5–50 mm.
[0016] Preferably, the polyimide filaments, glass fiber filaments, or braided tapes may also be pretreated; Pretreatment includes low-temperature plasma treatment and silane coupling agent treatment.
[0017] Preferably, the low-temperature plasma treatment includes the following steps: Polyimide filaments, glass fiber filaments, or braided tapes are wound around the drum electrodes of a plasma treatment device, and the treatment is carried out for 30 to 120 seconds at a radio frequency power of 50 to 300W and a discharge frequency of 5 to 40MHz.
[0018] Preferably, the silane coupling agent treatment includes the following steps: Mix the silane coupling agent with a mixture of deionized water and ethanol, adjust the pH to 4.5–5.5, and stir to hydrolyze to obtain a silane coupling agent treatment solution with a concentration of 0.5 wt%–3 wt%. Immerse polyimide filaments, glass fiber filaments, or braided tapes in the silane coupling agent treatment solution for 2–3 minutes, and then dry to obtain the final product. The silane coupling agents include at least one of KH-550, KH-560, KH-570 and A187.
[0019] Preferably, the polyimide filament may further include modified polyimide filament, prepared by the following steps: The boron nitride nanoparticles were added to dimethylacetamide solvent at a ratio of 0.5–5 g / 100 mL and ultrasonically dispersed. At the same time, 1–10% of the mass of the boron nitride nanoparticles was added to the surface for surface modification. The well-dispersed boron nitride nano suspension was mixed with diamine monomer, and the molar ratio of diamine monomer to pyromellitic dianhydride was controlled at (0.95~1.05):1. Pyromellitic dianhydride was slowly added, and the reaction temperature was controlled below 25℃. The mixture was stirred until the viscosity of the system was stable to obtain a polyamic acid solution with uniformly dispersed boron nitride nano. The adhesive solution is spun into a filament and then heated to complete the thermal imidization process, thereby obtaining modified polyimide filaments. The diamine monomers include diaminodiphenyl ether and diaminodiphenyl sulfide.
[0020] Preferably, the boron nitride nanoparticles have a particle size of <100nm and a boron nitride nanoparticle doping amount of 1% to 5%.
[0021] Preferably, the heating program includes: heating from 80°C to 100°C over 0.5 to 1 hour, and then heating to 300°C at a rate of 50°C / hour, with each temperature gradient held for 20 to 30 minutes.
[0022] Secondly, the present invention also discloses a preparation method, comprising the following steps: S1. Raw material pretreatment: Equilibrate glass fiber filaments and polyimide filaments under constant temperature and humidity conditions; S2. Preparation of blended yarn: Two filaments are fed into spinning equipment in proportion and blended yarn is made by ring spinning, Siro spinning or wrapping spinning process. S3. Braided tape weaving: Weaving blended yarns into braided tapes of the required specifications; S4. Post-processing: Heat setting treatment is performed on the woven tape.
[0023] Preferably, in the blended yarn preparation step, the twist is controlled to be 300-800 twists / meter.
[0024] Preferably, the heat setting temperature of the post-treatment is 20-30°C lower than the glass transition temperature of the polyimide filament used.
[0025] Thirdly, the present invention also discloses the application of polyimide-glass fiber blended braided tape in the inter-turn insulation, interlayer insulation or ground insulation of superconducting coils.
[0026] The beneficial effects of this invention are: 1. Improved thermal management performance: The polyimide filaments and glass fibers are microscopically interwoven inside the yarn to form a continuous, three-dimensional heat conduction network without significant interfaces. This effectively reduces the interfacial thermal resistance in traditional laminated structures, which is conducive to the rapid dissipation of heat during the operation of superconducting coils and improves the stability of the magnet.
[0027] 2. Synergistic optimization of mechanical properties: Glass fiber provides high stiffness and strength, while polyimide filament provides toughness and fatigue resistance. The combination of the two at the microscale achieves a balance of rigidity and flexibility, which can more effectively withstand the complex stresses brought about by winding, cooling and electromagnetic force impact, and reduce the risk of insulation cracking.
[0028] 3. High electrical insulation reliability: Polyimide itself has excellent dielectric properties, and when blended with insulating glass fiber, it forms a uniform insulator. The blended structure avoids potential local defects in the film, and the dielectric strength remains stable under liquid helium low temperature and high electric field.
[0029] 4. Excellent impregnation and processability: The uniform structure and controllable porosity of the single-material braided tape provide a continuous channel for low-temperature impregnation resins (such as epoxy resin and cyanate ester), facilitating complete and uniform impregnation and forming a dense and defect-free insulating whole. At the same time, it simplifies the winding process and improves production efficiency. Attached Figure Description
[0030] Figure 1 A schematic diagram of the insulation structure after superconducting coil winding and impregnation using the braided tape of the present invention; Figure 2 A schematic diagram of the mold winding structure using the woven tape of the present invention; Figure 3 This is a schematic diagram of the twill weave structure in Embodiment 2 of the present invention; Figure 4 (a) A traditional thin-film-glass fiber composite insulation structure, and (b) a schematic diagram of the heat conduction path of the blended woven tape insulation structure of the present invention. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0032] An insulating polyimide-glass fiber blended braided tape, the tape being woven from yarns made by blending polyimide filaments and glass fiber filaments; The mass ratio of polyimide filament to glass fiber filament is (30-50):(70-50).
[0033] By adopting the above technical solutions, polyimide filaments and glass fiber filaments achieve uniform blending at the microscale during the spinning stage, and then are woven into an integrated braided tape. This fundamentally eliminates the physical interface in the traditional polyimide film and glass fiber braided tape laminated structure, allowing heat to form a continuous three-dimensional conduction path along the fiber-resin matrix, effectively reducing radial thermal resistance and improving the quench protection and thermal stability of the superconducting coil. At the same time, the high stiffness of glass fiber and the low-temperature toughness of polyimide filaments achieve a mechanical synergy of rigidity and flexibility at the yarn scale, which can more effectively withstand the complex stresses brought about by winding, cooling and electromagnetic force impact, reducing the risk of insulation cracking. In addition, the uniform structure and controllable porosity of the single-material braided tape provide a continuous channel for low-temperature impregnation resin, making it easy to achieve completely uniform impregnation, avoiding the generation of local air gaps and weak points, and simplifying the winding process and improving production efficiency.
[0034] The polyimide-glass fiber blended braided tape of this application can be used for inter-turn insulation, inter-layer insulation, or ground insulation of superconducting coils, such as... Figure 1 As shown, in practical applications, the braided tape of this application can be wound with superconducting coils and impregnated to form an insulating structure. Its integrated blended structure eliminates the physical interface of traditional thin film-glass fiber lamination, avoiding interlayer debonding and microcracks caused by thermal shrinkage mismatch under liquid helium temperature cycling; the uniform interlacing of yarns allows for controllable inter-turn thickness and uniform electric field distribution; the porous structure facilitates full resin impregnation and filling, resulting in a dense, air-gap-free structure after curing; at the same time, the three-dimensional fiber network can quickly conduct superconducting heat, preventing hot spot accumulation, and single-tape winding replaces double-layer lamination, simplifying the process and reducing the insulation footprint.
[0035] In some embodiments, the polyimide filament is a thermoplastic polyimide filament with a glass transition temperature of not less than 250°C.
[0036] The glass fiber filaments are alkali-free glass fiber (E-glass) or high-strength glass fiber (S-glass), with a single filament diameter of 5 to 13 μm.
[0037] By adopting the above technical solutions, the glass transition temperature of thermoplastic polyimide filaments is not lower than 250℃, which can maintain sufficient dimensional stability and structural integrity in subsequent heat setting and superconducting magnet operation environments. At the same time, it can still maintain the necessary toughness to absorb electromagnetic cyclic stress at liquid helium temperature. Alkali-free glass fiber or high-strength glass fiber has excellent electrical insulation and high modulus characteristics. The single filament diameter is controlled within the range of 5 to 13 μm, which not only ensures the softness and spinnability of the fiber, making the blended yarn structure tight and uniform, but also provides sufficient mechanical support in the braided tape. This ensures that the braided tape has stable electrical insulation performance, good mechanical strength and excellent fatigue resistance under extreme low temperature, strong field and high mechanical stress conditions.
[0038] In some embodiments, the blend includes one of ring spinning, Siro spinning, and wrapping spinning; when the wrapping spinning process is used, the polyimide filament is the core yarn and the glass fiber filament is the covering yarn.
[0039] By adopting the above technical solutions, the three blending processes of ring spinning, Siro spinning, and wrapping spinning can be flexibly selected according to the mechanical properties and structural characteristics required for the woven tape. Among them, Siro spinning combines and twists polyimide filaments and glass fiber filaments in the drafting zone to form a tightly structured and uniformly mixed yarn, effectively improving the cohesion between fibers and the weaving adaptability. Wrapping spinning uses polyimide filaments as the core yarn and glass fiber filaments as the covering yarn, which can form a core-sheath structure that is tough inside and tough outside. The polyimide filaments in the core layer provide excellent electrical insulation and low-temperature toughness, while the glass fiber filaments in the outer layer give the yarn high modulus and high strength. At the same time, the covering layer can also protect the core yarn from mechanical damage during the weaving process, so that the final woven tape has both good mechanical support and stable insulation performance.
[0040] In some embodiments, the woven tape has a plain weave, twill weave, or satin weave structure, with a thickness of 0.05–0.20 mm and a width of 5–50 mm.
[0041] By adopting the above technical solutions, the three weaving structures of plain weave, twill weave, and satin weave can be selected according to the mechanical requirements of the superconducting coil and the characteristics of the resin impregnation process. The plain weave structure has many interlacing points and stable structure, which is conducive to ensuring the dimensional stability and shear resistance of the braided tape. The twill weave structure is soft and has good extensibility, which can better fit the coil surface and absorb stress. The satin weave structure has a smooth surface and the continuous channels formed by the internal floating long lines are conducive to the capillary penetration and flow of the impregnating resin, thereby achieving uniform and sufficient impregnation.
[0042] In some embodiments, the polyimide filaments, glass fiber filaments, or braided tapes may also be pretreated; Pretreatment includes low-temperature plasma treatment and silane coupling agent treatment.
[0043] By employing the above technical solutions, low-temperature plasma treatment can introduce polar active groups such as hydroxyl, carboxyl, or amino groups onto the surface of polyimide or glass fiber filaments, effectively increasing the fiber surface energy and roughness, thereby significantly improving the wettability and physical anchoring effect between the fiber and the subsequent impregnation resin. Silane coupling agent treatment can form a molecular bridging layer on the fiber surface, with one end chemically bonded to the fiber's active groups and the other end reacting or entangled with the resin matrix, transforming the fiber-resin bond from a simple physical combination to a synergistic effect of chemical bonding and physical adsorption. These pretreatments can be applied to filaments before blending to enhance the bonding force between fibers within the yarn, or to the entire braided tape after weaving to strengthen the interfacial adhesion between the braided tape and the impregnation resin. Ultimately, this results in an insulating layer with higher interlaminar shear strength and better interfacial durability after impregnation and curing, effectively avoiding the risk of interface debonding or resin cracking in superconducting magnets under long-term thermal cycling and electromagnetic forces.
[0044] In some embodiments, low-temperature plasma treatment includes the following steps: Polyimide filaments, glass fiber filaments, or braided tapes are wound around the drum electrodes of a plasma treatment device. The treatment is performed at an RF power of 50–300W, a discharge frequency of 5MHz–40MHz, and for 30–120 seconds. More specifically, the RF power is 100W, the discharge frequency is 13.56MHz, and the treatment lasts 30–120 seconds. By adopting the above technical solutions, plasma treatment can generate appropriate physical etching and chemical activation on the fiber surface, effectively introduce oxygen-containing polar groups and improve surface roughness, and ultimately enable the plasma-treated braided tape to achieve rapid resin penetration and uniform filling during vacuum pressure impregnation. The insulation layer after impregnation and curing has higher interlaminar shear strength and interfacial bonding reliability.
[0045] In some embodiments, the silane coupling agent treatment includes the following steps: Mix the silane coupling agent with a mixture of deionized water and ethanol, adjust the pH to 4.5–5.5, and stir to hydrolyze to obtain a silane coupling agent treatment solution with a concentration of 0.5 wt%–3 wt%. Immerse polyimide filaments, glass fiber filaments, or braided tapes in the silane coupling agent treatment solution for 2–3 minutes, and then dry to obtain the final product. The silane coupling agent includes at least one of KH-550, KH-560, KH-570 and A187.
[0046] By adopting the above technical solution, the silane coupling agent is fully hydrolyzed in a weakly acidic ethanol-water mixture to generate silanol groups. These groups can undergo dehydration condensation reaction with the silanol groups on the surface of the glass fiber, thereby firmly anchoring the coupling agent molecular layer on the fiber surface. The other end of this molecular layer contains epoxy groups, which can form chemical bonds with the subsequently impregnated epoxy resin matrix during the ring-opening curing process, thus building a stable chemical bridge between the fiber and the resin.
[0047] In some embodiments, the polyimide filament may further comprise a modified polyimide filament, prepared by the following steps: The boron nitride nanoparticles were added to dimethylacetamide solvent at a ratio of 0.5–5 g / 100 mL and ultrasonically dispersed. At the same time, 1–10% of the mass of the boron nitride nanoparticles was added to the surface for surface modification. The well-dispersed boron nitride nano suspension was mixed with diamine monomer, and the molar ratio of diamine monomer to pyromellitic dianhydride was controlled at (0.95~1.05):1. Pyromellitic dianhydride was slowly added, and the reaction temperature was controlled below 25℃. The mixture was stirred until the viscosity of the system was stable to obtain a polyamic acid solution with uniformly dispersed boron nitride nano. The adhesive solution is spun into a filament and then heated to complete the thermal imidization process, thereby obtaining modified polyimide filaments. The diamine monomers include diaminodiphenyl ether and diaminodiphenyl sulfide.
[0048] The particle size of the nano boron nitride is <100nm, and the doping amount of the nano boron nitride is 1% to 5%.
[0049] The heating program includes: heating from 80℃ to 100℃ over 0.5 to 1 hour, and then heating to 300℃ at a rate of 50℃ / hour, with each temperature gradient held for 20 to 30 minutes.
[0050] By adopting the above technical solutions, boron nitride nanoparticles, after ultrasonic dispersion and diamine monomer surface modification, are uniformly dispersed in polyamic acid liquid through in-situ polymerization. This effectively avoids the agglomeration and sedimentation of nanofillers, enabling the thermally conductive filler to form a continuous and interconnected thermally conductive network in the polyimide matrix. Doping with boron nitride nanoparticles can significantly improve the radial thermal conductivity of polyimide filaments. Furthermore, as a wide-bandgap inorganic insulating filler, boron nitride nanoparticles have extremely high intrinsic volume resistivity. While forming thermally conductive pathways in the polyimide matrix, they do not introduce conductive channels. Therefore, while significantly improving the thermal conductivity, it can maintain or even optimize the excellent electrical insulation properties of polyimide, ensuring that the blended woven tape still has stable dielectric strength and corona resistance under liquid helium low-temperature and high-electric-field environments. In addition, the uniform dispersion of nanoparticles in the polyamic acid liquid can play a physical reinforcement and barrier effect in the imidized polyimide matrix, improving the mechanical modulus, dimensional stability, and solvent penetration resistance of the film.
[0051] A preparation method comprising the following steps: S1. Raw material pretreatment: Equilibrate glass fiber filaments and polyimide filaments under constant temperature and humidity conditions; S2. Preparation of blended yarn: Two filaments are fed into spinning equipment in proportion and blended yarn is made by ring spinning, Siro spinning or wrapping spinning process. S3. Braided tape weaving: Weaving blended yarns into braided tapes of the required specifications; S4. Post-processing: Heat setting treatment is performed on the woven tape.
[0052] In some embodiments, during the blended yarn preparation step, the twist is controlled to be 300 to 800 twists / meter.
[0053] By adopting the above technical solutions, the twist of the blended yarn is controlled within the range of 300 twists / meter to 800 twists / meter. This allows the polyimide filament and glass fiber filament to achieve appropriate cohesion and structural compactness, avoiding problems such as yarn loosening, fiber slippage, and weaving breakage caused by excessively low twist. At the same time, it prevents excessively high twist from causing excessively stiff yarn, reduced softness, and fiber damage. Within this twist range, the blended yarn maintains good weaving adaptability and dimensional stability of the braided tape, while also forming a uniform and controllable porous structure inside the braided tape. This provides a continuous and unobstructed channel for the capillary penetration and uniform filling of the resin during the subsequent vacuum pressure impregnation process. Ultimately, this results in a dense and defect-free insulation layer after impregnation and curing, possessing excellent mechanical strength, interlaminar shear properties, and thermal conductivity.
[0054] In some embodiments, the heat setting temperature of the post-treatment is 20–30°C lower than the glass transition temperature of the polyimide filament used.
[0055] By adopting the above technical solutions, setting the heat setting temperature to 20-30°C below the glass transition temperature of polyimide filaments can effectively eliminate the internal stress generated by warp and weft interlacing and tension during the weaving process of the braided tape without damaging the molecular chain structure and mechanical properties of the polyimide filaments. This makes the size and shape of the braided tape more stable and prevents uncontrollable thermal shrinkage or structural deformation during subsequent vacuum pressure impregnation and low-temperature thermal cycling. At the same time, this temperature range is sufficient to allow the fiber arrangement and twist structure in the yarn to be appropriately relaxed and fixed, improving the flatness and softness of the braided tape, making it easier to achieve tight bonding and semi-overlapping winding during the superconducting coil winding process, and ultimately ensuring the uniformity of the insulation layer thickness and the consistency of the structure.
[0056] Example Example 1: An insulating polyimide-glass fiber blended braided tape is prepared through the following steps: E-glass fiber filament (EC8-136, 8μm monofilament diameter) was used, accounting for 60 parts by weight; thermoplastic polyimide filament (Hyplon M500) was used, accounting for 40 parts by weight. After equilibration of the two filaments at 22±2℃ and 60±5% relative humidity for 24 hours, a blended yarn was directly produced using ring spinning, with a twist of 600 twists / meter. The blended yarn was woven into a plain weave tape with a thickness of 0.12mm and a width of 20mm, with a warp and weft density of 100 warp ends / 10cm and 90 weft ends / 10cm. Heat setting at 255℃ for 5 minutes yielded an insulating polyimide-glass fiber blended tape.
[0057] The braided tape is impregnated with epoxy resin VPI: the braided tape is wrapped around a stainless steel plate in a semi-overlapping manner, with a wrapping thickness of 5mm. The compression rate is calculated at 20%, resulting in a designed compressed thickness of 4mm. Figure 2 As shown. The steel plate was placed in an impregnation mold and then placed in a vacuum impregnation furnace. It was preheated and degassed for 2 hours at 100℃ and a vacuum degree ≤100Pa. A mixture of low-viscosity bisphenol A epoxy resin and anhydride curing agent (methyltetrahydrophthalic anhydride) was injected (resin to curing agent mass ratio 100:85, viscosity 300~500 mPa·s at 25℃), and the impregnation time was 4 hours. Then, it was held under 0.6 MPa pressure for 2 hours, and cured according to the following procedure: 80℃ for 2 hours, 120℃ for 3 hours, and 150℃ for 4 hours. The radial thermal conductivity at 77K was measured to be 0.96 W / (m·K) (according to ASTM E1461 flash test), the interlaminar shear strength (ILSS) was 95 MPa (according to ASTM D2344 short beam shear test), and the breakdown strength was 42 kV / mm (according to GB / T 1408.1, power frequency withstand voltage). This demonstrates that even without surface treatment, the polyimide-glass fiber blended woven tape of the present invention still possesses acceptable insulation, mechanical, and thermal properties.
[0058] Example 2: An insulating polyimide-glass fiber blended woven tape is prepared through the following steps: S-glass fiber filaments (9μm diameter per filament) surface-treated with silane coupling agent KH-560 were used, accounting for 65 parts by weight. The treatment process was as follows: The 9μm diameter S-glass filaments were placed in a 120℃ oven for 30 minutes. KH-560 was mixed with deionized water / ethanol (1:1 mass ratio), and the pH was adjusted to 5 with acetic acid. The mixture was stirred and hydrolyzed for 15 minutes to obtain a 2% concentration treatment solution. The glass fiber filaments were then passed through the treatment solution at a uniform speed, with the immersion time controlled at 3 minutes to ensure sufficient contact between the coupling agent and the hydroxyl groups on the fiber surface. After removal, the filaments were pre-dried at 110℃ for 10 minutes to remove the solvent, and then dried at 160℃ for 20 minutes to complete the chemical bonding between the coupling agent and the glass fiber. After cooling, the filaments were sealed for later use.
[0059] High thermal conductivity polyimide filaments (Hyplon M500 modified) doped with boron nitride (BN) nanofiller (particle size <100nm, doping amount 3wt%) were selected, accounting for 35 parts by weight. The doping method was in-situ polymerization: BN nanoparticles (particle size 50~100nm) were added to dimethylacetamide solvent at a rate of 2g / 100mL and ultrasonically dispersed for 30min. At the same time, diamine monomers accounting for 5% of the mass of BN nanoparticles were added for surface modification to avoid agglomeration. The dispersed BN suspension was mixed with diaminodiphenyl ether, and the molar ratio of diaminodiphenyl ether to pyromellitic dianhydride was controlled at 1:1. Pyromellitic dianhydride was slowly added, and the reaction temperature was controlled below 25℃. The mixture was stirred until the viscosity of the system stabilized to obtain a polyamic acid solution with uniform BN dispersion. Spinning and forming: Polyamic acid filaments are produced by wet spinning of polyamic acid filaments, and then thermal imidization is completed by gradient heating at 80℃ for 1h → 100℃ / 150℃ / 200℃ / 250℃ / 300℃ for 30min each, to obtain BN-doped PI filaments.
[0060] Glass fiber filaments and BN-doped PI filaments were equilibrated for 24 hours at 22°C and 60% relative humidity. The two types of filaments were then fed into a spinning machine in a specific ratio and spun using a Sirospinning process. The two filaments were combined and twisted in the drafting zone to form a tightly structured, uniformly mixed yarn with a twist of 550 twists / meter. The blended yarn was then woven into a 2 / 2 double-sided twill weave (e.g.,...). Figure 3 As shown), the thickness is 0.15mm and the width is 35mm. The woven tape is heat-set at 300℃ for 30 minutes to obtain the desired product.
[0061] The braided tape was impregnated with epoxy resin VPI: the braided tape was wrapped around a stainless steel plate in a semi-overlapping manner, with a winding thickness of 5mm. The compression rate was calculated at 20%, and the designed compression thickness was 4mm. The steel plate was placed in an impregnation mold and then placed in a vacuum impregnation furnace. It was preheated and degassed for 2 hours at 100℃ and a vacuum degree ≤100Pa. A mixture of low-viscosity bisphenol A type epoxy resin and anhydride curing agent (methyltetrahydrophthalic anhydride) was injected (resin to curing agent mass ratio 100:85, viscosity at 25℃ 300~500mPa·s), and the impregnation time was 4 hours. Then, it was held under 0.6MPa pressure for 2 hours and cured according to the following procedure: 80℃ for 2 hours, 120℃ for 3 hours, and 150℃ for 4 hours.
[0062] The radial thermal conductivity of the hybrid tape sample at 77K was measured to be 1.05 W / (m·K) (according to ASTM E1461 flash test), which is approximately 28% higher than that of the conventional composite structure sample in Comparative Example 1 (0.82 W / (m·K)). The ILSS at 77K was 105 MPa (according to ASTM D2344 short beam shear test), which is approximately 18% higher than that of Comparative Example 1 (89 MPa). The breakdown strength was 45 kV / mm (according to GB / T1408.1, power frequency withstand voltage), meeting the insulation requirements of superconducting coils. The specific preparation method of Comparative Example 1 is described in Comparative Example 1.
[0063] The design requirements for inter-turn / inter-layer insulation of high-field superconducting magnets in this embodiment are: radial thermal conductivity ≥ 0.9 W / (m·K) at 77K, inter-layer shear strength (ILSS) ≥ 90 MPa at 77K, and breakdown strength ≥ 40 kV / mm. The measured results all meet the above design requirements and show a significant improvement over traditional GK composite tapes.
[0064] Example 3: An insulating polyimide-glass fiber blended woven tape is prepared through the following steps: E-glass fiber filaments (7μm diameter per filament) were used, accounting for 55 parts by weight. Copolymer polyimide filaments with excellent low-temperature toughness (Tg=330℃, Hyplon M500) were selected, accounting for 45 parts by weight.
[0065] Low-temperature plasma surface treatment was performed on both types of fibers: glass fiber filaments and polyimide filaments were wound onto the roller electrodes of the plasma treatment equipment. The working gas was a mixture of 99.99% high-purity oxygen and 5% argon (volume ratio O2:Ar=95:5), with a total gas flow rate of 100 sccm, the oxygen partial pressure in the chamber controlled at 20 Pa, the RF power supply power of 100 W, the discharge frequency of 13.56 MHz, and the treatment time of 60 s. After treatment, the fibers were stored in a desiccator. A wrapping spinning process was used, with polyimide filaments as the core and glass fiber filaments wrapped around it in the opposite direction at a twist of 650 twists / meter, forming a core-sheath structure yarn that is tough inside and rigid outside. The yarn was then heat-set at 260℃ for 5 min. The yarns were woven into a 5-end, 3-fly warp-faced satin weave (i.e., each warp yarn crosses 5 weft yarns and sinks 3, with a warp float length of 5). The warp and weft density was set at 120 warp threads / 10cm and 72 weft threads / 10cm, with a thickness of 0.13mm and a width of 25mm. The satin weave has a smooth surface, and the internal channels facilitate resin flow.
[0066] The woven tape was impregnated with epoxy resin using VPI (Vacuum Injection Polymerization): The woven tape was cut into 200mm × 200mm samples and preheated and degassed in a vacuum impregnation tank at 80℃ and a vacuum degree ≤100Pa for 1.5 hours. Epoxy resin solution (bisphenol A type epoxy resin E-51 and methyltetrahydrophthalic anhydride curing agent mass ratio 100:85, viscosity 300~500 mPa·s at 25℃) was injected for 3 hours, followed by pressure holding at 0.5 MPa for 2 hours, and then curing at 80℃ for 2 hours, 120℃ for 3 hours, and 150℃ for 4 hours. After this fiber plasma treatment, the contact angle of the woven tape to the epoxy resin was 8° (according to GB / T 30693 contact angle measurement method), exhibiting superhydrophilicity. The impregnated samples showed a resin filling rate ≥98% and no visible pores. At a liquid helium temperature of 4.2K, its elongation at break is 3.2%, which is 33% higher than that of the conventional structural insulation sample in Comparative Example 1.
[0067] The design requirements for low-temperature toughness and high impregnation of large scientific research magnets in this embodiment are: elongation at break at 4.2K ≥ 2.5%, resin filling rate ≥ 95%, and contact angle ≤ 15°. Actual test results show: elongation at break at 4.2K 3.2% (exceeding the design requirement by 28%), resin filling rate ≥ 98%, and contact angle 8°, all meeting the design requirements.
[0068] Comparative Example Comparative Example 1: Traditional GK composite tape (polyimide film-glass fiber woven tape composite structure) Traditional composite structure samples were prepared using existing technology: a 25 μm thick polyimide film (Kapton HN) and a plain-weave glass fiber tape (monofilament diameter 9 μm, areal density 200 g / m²) were used. 2 The layers (0.15mm thick and 35mm wide) are stacked to form a GK composite tape with a total thickness of approximately 0.175mm.
[0069] The composite tape was impregnated and cured using the same epoxy resin VPI impregnation process as in Example 1. Tests showed that the radial thermal conductivity of the Comparative Example 1 sample at 77K was 0.82 W / (m·K), the ILSS was 89 MPa, the breakdown strength was 42 kV / mm, and the elongation at break at 4.2K was 2.4%.
[0070] The aforementioned traditional GK composite tapes typically need to meet the same design requirements as the examples described: radial thermal conductivity ≥0.9 W / (m·K) at 77K, interlaminar shear strength (ILSS) ≥90 MPa at 77K, breakdown strength ≥40 kV / mm, and elongation at break ≥2.5% at 4.2K. However, actual test results show that due to the presence of a distinct interface, the thermal conductivity, interlaminar shear strength, and low-temperature toughness of the GK composite tapes do not meet the design requirements or are at a critical level. Figure 4It is known that in traditional laminated structures, there is a distinct interface between the polyimide film and the glass fiber braided tape. Heat must cross multiple interfaces to be transferred radially, resulting in high interfacial thermal resistance and a tortuous heat flow path. In the blended braided tape of this invention, the polyimide filaments and glass fiber filaments are uniformly interwoven at the yarn scale to form a continuous and interconnected three-dimensional heat-conducting network, eliminating the significant interface. Heat can be rapidly conducted along the fiber-resin matrix, effectively reducing radial thermal resistance and improving the quench protection and thermal stability of the superconducting coil.
[0071] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. An insulating polyimide-glass fiber blended woven tape, characterized in that, The woven tape is made of yarn woven from a blend of polyimide filaments and glass fiber filaments; The mass ratio of the polyimide filament to the glass fiber filament is (30-50):(70-50).
2. The polyimide-glass fiber blended woven tape according to claim 1, characterized in that, The polyimide filament is a thermoplastic polyimide filament with a glass transition temperature of not less than 250°C; the glass fiber filament is an alkali-free glass fiber or a high-strength glass fiber with a single filament diameter of 5–13 μm.
3. The polyimide-glass fiber blended woven tape according to claim 1, characterized in that, The blended yarn includes one of ring spinning, Siro spinning, and wrapping spinning; when the wrapping spinning process is used, the polyimide filament is the core yarn and the glass fiber filament is the covering yarn.
4. The polyimide-glass fiber blended woven tape according to claim 1, characterized in that, The woven tape has a plain weave, twill weave, or satin weave structure, with a thickness of 0.05–0.20 mm and a width of 5–50 mm.
5. The polyimide-glass fiber blended woven tape according to claim 1, characterized in that, The polyimide filament, glass fiber filament, or woven tape may also undergo pretreatment; The pretreatment includes low-temperature plasma treatment and silane coupling agent treatment.
6. The polyimide-glass fiber blended woven tape according to claim 5, characterized in that, The low-temperature plasma treatment includes the following steps: Polyimide filaments, glass fiber filaments, or braided tapes are wound around the drum electrodes of the plasma treatment equipment, and the radio frequency power is 50-300W, the discharge frequency is 5MHz-40MHz, and the treatment time is 30-120s. The silane coupling agent treatment includes the following steps: Mix the silane coupling agent with a mixture of deionized water and ethanol, adjust the pH to 4.5–5.5, and stir to hydrolyze to obtain a silane coupling agent treatment solution with a concentration of 0.5 wt%–3 wt%. Immerse polyimide filaments, glass fiber filaments, or braided tapes in the silane coupling agent treatment solution for 2–3 minutes, and then dry to obtain the final product. The silane coupling agent includes at least one of KH-550, KH-560, KH-570 and A187.
7. The polyimide-glass fiber blended woven tape according to claim 1, characterized in that, The polyimide filament may further include modified polyimide filaments, which are prepared through the following steps: The boron nitride nanoparticles were added to dimethylacetamide solvent at a ratio of 0.5–5 g / 100 mL and ultrasonically dispersed. At the same time, 1–10% of the mass of the boron nitride nanoparticles was added for surface modification. The well-dispersed boron nitride nano suspension was mixed with diamine monomer, and the molar ratio of diamine monomer to pyromellitic dianhydride was controlled at (0.95~1.05):
1. Pyromellitic dianhydride was slowly added, and the reaction temperature was controlled below 25℃. The mixture was stirred until the viscosity of the system was stable to obtain a polyamic acid solution with uniformly dispersed boron nitride nano. The adhesive solution is spun into a filament and then heated to complete the thermal imidization process, thus obtaining modified polyimide filaments. The diamine monomers include diaminodiphenyl ether and diaminodiphenyl sulfide.
8. A preparation method for preparing the insulating polyimide-glass fiber blended woven tape according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Raw material pretreatment: Equilibrate glass fiber filaments and polyimide filaments under a constant temperature and humidity environment; S2. Preparation of blended yarn: Two filaments are fed into spinning equipment in proportion and blended yarn is made by ring spinning, Siro spinning or wrapping spinning process. S3, Braided tape weaving: Weaving blended yarns into braided tapes of the required specifications; S4. Post-processing: Heat setting treatment is performed on the woven tape.
9. The preparation method according to claim 8, characterized in that, In the process of preparing the blended yarn, the twist is controlled to be 300-800 twists / meter; The heat setting temperature of the post-treatment is 20-30°C lower than the glass transition temperature of the polyimide filament used.
10. The application of the polyimide-glass fiber blended braided tape according to any one of claims 1 to 7 in the inter-turn insulation, interlayer insulation or ground insulation of superconducting coils.